RELACIÓN DE LOS ESTILOS DE LIDERAZGO CON EL DESEMPEÑO DE LOS SERVIDORES Y TRABAJADORES DE LA DIRECCIÓN PROVINCIAL DEL INSTITUTO ECUATORIANO DE SEGURIDAD SOCIAL DE MORONA SANTIAGO, DURANTE EL PERÍODO 2015-2016 - Galeas Galeas, Norma Cumandá (2017)
The institutions of the state of Ecuador have been modernizing to improve the quality of their services to the community, being important the investigation of the styles of leadership that are used to identify them in those organizations that fail, are maintained or that achieve the success when fulfilling his objectives. The measurement models are applied to determine the perception that can have a group of people on a marked style of leadership. This paper aims to reveal if the leadership style of the authority is related to the better performance of the organization's staff, for which the study used the qualitative methodology with an empirical-analytical approach, for which a survey of 30 employees of a public institution on the factors that impact on their performance, from the perspective of the authoritarian or democratic leadership style. It will deal with the concepts, qualities and generalities of leadership and work performance recognized by the scientific community. The different styles of leadership will be analyzed to conclude that a democratic style implanted strategically or spontaneously, obtains a better work performance of the servants.